Lebende Bilder und Attitüden in Fotografie, Film und Video Tableaux Vivants - Folie, Sabine; Glasmeier, Michael; Matt, Gerald; Reissberger, Mara; Kunsthalle Wien, Wien (Wien : VBK, 2002)
Cameron, Julia Margaret ; Wynfield, David Wilkie ; Pathé, Gebrüder ; Valentin, Karl ; Duchamp, Marcel ; Ray, Man ; Madame Yevonde ; Cahun, Claude ; Magritte, René ; Arndt, Gertrud
Lebende Bilder und Attitüden in Fotografie, Film und Video, Kunsthalle Wien, Wien, 24. Mai 2002 - 28. August 2002
kunstcatalogus